Inclusive ethnography : making fieldwork safer, healthier and more ethical - Procter, Caitlin; Spector, Branwen (London: Sage, 2024)
"In this nuanced, candid book, researchers from across the globe discuss core challenges faced by ethnographers, reflecting on research from preparation to dissemination and how identity interacts with the realities of doing fieldwork"--
Keywords: Ethnograph